Post-soviet habitus heterogeneity on the example of Slavyansk armed conflict: methodological framework of research - Работягова, І. В.; Кисельова, В. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article explores an opportunity to apply the methodology of structuralism, especially habitus concept, to Ukrainian-Russian armed conflict analyses. On the example of Sloviansk war events during April-July 2014 the heterogeneity of Post-Soviet habitus is shown. Such phenomenon is also considered as being a precondition and an integrated part of modern hybrid war conflict.